Avaliação mesoscópica da origem, distribuição e ramificação do nervo radial no braço do gato doméstico (Felis catus domesticus, Linnaeus, 1758) - Guimaraes, Gregorio Correa; Fernandes Machado, Marcia Rita [UNESP]; Quaqliatto Santos, Andre Luiz (Universidade Federal de Uberlândia (UFU), 2008)
The present study evaluated the origin, distribution and ramification of the radial nerves were studied in 30 adult domestic cats. The sample included 15 females and 15 males of unknown breed. The specimens were fixed in 10% formaldehyde solution. The radial nerve showed many fascicles from the origin also your ramification in superficial and deep branches. Radial nerves were observed to originate, in 16 cases (26.7%), from the ventral branch of the sixth cervical spinal nerve; in 60 cases (100%), from the ventral branch of the seventh cervical spinal nerve; in 60 cases (100%), from the ventral branch of the eight cervical nerve and in 60 cases (100%), from the ventral branch of the first thoracic nerve. The radial nerves branched out, in all of the animals studied (100.0%), to the tensor fasciae antebrachii, long, accessory, medial and lateral heads of the triceps branchii and anconeus muscles. The radial nerve emits of 14 to 25 nervous branches in this region. However, the branch of the sixth cervical spinal nerve and the nervous fascicles reveal significant differences (p <= 0.05), respectively, in or with relation to sex of the animals and the studied region.

No presente estudo avaliou-se a origem, a distribuição e a ramificação do nervo radial de 30 gatos adultos, 15 machos e 15 fêmeas, sem raça definida, mediante dissecação mesoscópica, após a fixação dos espécimes em solução aquosa de formaldeído a 10%. O referido nervo mostrou-se polifasciculado desde a origem até sua ramificação em ramos superficial e profundo. Sua origem ocorreu a partir dos ramos ventrais do sexto (26,7%), sétimo (100,0%) e oitavo (100,0%) nervos espinhais cervicais e do ramo ventral do primeiro (100,0%) nervo espinhal torácico. Na região do braço, o nervo radial cedeu ramos musculares em todos os animais (100,0%) para os músculos tensor da fáscia do antebraço, cabeça longa do tríceps braquial, cabeça acessória do tríceps braquial, cabeça medial do tríceps braquial, cabeça lateral do tríceps braquial e ancôneo, emitindo de 14 a 25 ramos nervosos nesta região. O ramo ventral do sexto nervo espinhal cervical apresentou diferença significativa (p0,05) em relação ao sexo dos animais, ocorrendo quase que exclusivamente nas gatas, além dos fascículos nervosos, que diferiram significativamente de acordo com a região estudada.
Mesoscopic evaluation of the radial nerve origin, distribution and ramification in the arm of the domestic cat (Felis catus Linnaeus, 1758)
Keywords: Mesoscopic; Radial nerve; Domestic cat